Implementing a Made-in-New Brunswick Outdoor Environmental Education Program: A Case Study of Salem Elementary School - Gillis, Natalie Y. (Journal of New Brunswick Studies / Revue d’études sur le Nouveau-Brunswick, 2016)
An increasing amount of academic literature has documented a growing disconnect between youth and the outdoor/natural world, particularly when it comes to their formal education. This disconnect has been called “nature deficit disorder” (NDD), a term that highlights the importance of interaction with the natural world for a person’s health, development, and well-being, as well as environmental sensitivity and responsibility. This paper argues, using a New Brunswick-based case study, that outdoor learning facilities and environmental education at our schools can combat the detrimental effects of NDD. Salem Elementary School in Sackville, New Brunswick, is used as a case study. To combat NDD by increasing student interactions with the natural world, a community-based partnership developed and implemented an outdoor learning facility and outdoor education program. The paper uses qualitative research methods to document the implementation and outcomes of the program through a year-long observation of the project. The paper also offers recommendations for schools wishing to develop their own outdoor education program and for the Department of Education and faculties of education.